As an online market place, the customer servicer acivities & customer satisfaction of Kaymu.com.bd - Ahamed, Arif (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.